PENGUJIAN MODEL SIMULASI VIGOR KEKUATAN TUMBUH BENIH KEDELAI (Glycine max (L) Merril) PADA KONDISI LAHAN STRES OKSIGEN - Syamsuddin Syamsuddin; Syafruddin Syafruddin; Hasanuddin Hasanuddin (Jurnal Floratek, 2011)
The research objectives were to study relationships between soybean seed vigor in laboratory and seed growth in field.  The research was carried out in Laboratory Seed Science and Technology and Seed Experimental Farm of Agriculture Faculty, University of Syiah Kuala, Darussalam Banda Aceh. Experimental design used was a completely randomized design (CRD) 2x5 with 3 replications in the laboratory and a split plot design with 3 replications in the field. The factors examined were soybean varieties and oxygen. The varieties were consisted of Pandermau S-37, Local of Bireuen, Wilis, Orba, local of Tasikmalaya. The oxygen was consisted of 2 levels, i.e. oxygen stress and normal oxygen. Variables observed in the laboratory were seedling growth rate and dry weight of normal seedling, while in the field were soybean growth rate and dry weight of plant.  Results showed that growth of the five varieties on the field of oxygen stress can be simulated through examination in laboratory. Of the two variables observed, seedling growth rate was more sensitive for the purpose. On the other hand, dry weight of seedling was less precise for simulating that condition.